SIKAP BAHASA SISWA BILLINGUAL: KAJIAN PSIKO-SOSIOLINGUISTIK DI LINGKUNGAN SEKOLAH MULTIKULTURAL: STUDI KASUS SD HIKMATUL FADHILLAH - Rahmah, Sayyidatur (Ihya al-Arabiyah: Jurnal Pendidikan Bahasa dan Sastra Arab, 2023)
This study examines the language attitudes of bilingual students in multicultural schools using a psycholinguistic perspective. The main issue of this study is how bilingual students' language attitudes are formed and the psychological and social factors that influence them in the context of multicultural education. The purpose of this study is to describe the patterns of bilingual students' language attitudes and explain the determinants of these attitudes. The method used is a systematic literature review of scientific publications from 2010 to 2024 that are relevant to language attitudes, bilingualism, and multicultural education. The findings show that students' language attitudes are multidimensional (cognitive, affective, and conative) and are influenced by language status and prestige, ethnolinguistic identity, peer influence, and school policy. The implications of this study emphasize the importance of additive bilingual education policies, strengthening teacher competencies, and creating an inclusive school language ecology.